Geometrical Aspect of Compressibility Critical Exponent - Yu, J. S.; Du, W. K.; Liu, Q. H. (Frontiers in Physics, 2022)
Critical exponent γ 1.1 characterizes behavior of the mechanical compressibility of a real fluid when temperature approaches the critical one. It results in zero Gaussian curvature of the local shape of the critical point on the thermodynamic equation of state surface, which imposes a new constraint upon the construction of the potential equation of state of the real fluid from the empirical data. All known empirical equations of state suffer from a weakness that the Gaussian curvature of the critical point is negative definite instead of zero.